Iron and manganese content in groundwater on the northeastern coast of the Buenos Aires Province, Argentina - Carretero, Silvina Claudia (2015)
The iron and manganese content in groundwater on the northeastern coast of the Buenos Aires Province, Argentina, was analyzed. Borehole sampling and chemical analyses were performed and evaluated based on the hydrogeological characteristics of the phreatic aquifer located in the coastal barrier, which is the only supply source to the population. Fe concentrations in groundwater fluctuate between 0.03 and 3.5 mg/L, with a mean value of 0.33 mg/L, whereas Mn varies between 0.03 and 1.20 mg/ L, with a mean value of 0.24 mg/L. There is a relationship between the geomorphological environments and the distribution of major ions, except the case of Fe and Mn. The sand that constitutes the aquifer contains pyroxenes, amphiboles, biotite, Fe oxides and hydroxides, and volcanic groundmass stained by hydroxides, all of which are the source of Fe and Mn—whose concentrations are unrelated to each other, to Ph or to Eh due to a state of redox disequilibrium. Possible health risks due to Fe and Mn excess in water are considered. According to the international guidelines for Fe, 38 % of the samples exceed the acceptable values, while 33 % exceed the Argentine standards. As regards Mn, the samples with excess Mn are 53 and 38 %, respectively. Further groundwater quality monitoring and chemical studies are necessary, especially regarding the evolution of Fe and Mn contents. To offer an adequate supply of drinking water to the population, it is necessary to remove Fe and Mn so that the concentrations are within the drinking water guidelines.